USE OF PLANTS AS TRADITIONAL MEDICINE IN SWAMEDICATION IN PIDIE COMMUNITIES - Hardiana Hardiana; Saida Rasnovi; Zumaidar Zumaidar (Universitas Syiah Kuala, 2019)
Self-medication is an act of self-healing using plants as traditional and modern medicine without the intervention of professional medical personnel. Availability of natural materials and affordable prices encourage people to return to using traditional medicines. The purpose of this study is to find out the types of plants used by the community Pidie, plant parts and reasons for using plants as traditional medicine in self-medication. The type of research used is non-experimental with the survey method and PRA (Participatory Rural Appraisal), by interviewing 1280 respondents. Parameters of this study are the types of plants used, plant parts and reasons for using plants as traditional medicine in self-medication. The results showed that there were 38 tribes and 53 types of plants. The most widely used plant parts were leaves (44.3%), the least were roots (0.7%), and the reason for using plants as traditional medicine in self-medication was easily obtained (53.8%).